Childhood Maltreatment and Adolescent Eating Disorders’ Symptoms: A Moderated Mediation Model of Social Anxiety and Physical Activity - Li S; Luo X; Song L; Gao X; Shen Y (Psychology Research and Behavior Management)
Sihong Li, Xuerong Luo, Lintong Song, Xueping Gao, Yanmei Shen Department of Psychiatry, National Clinical Research Center for Mental Disorders, and National Center for Mental Disorders, The Second Xiangya Hospital of Central South University, Changsha, Hunan, 410011, People’s Republic of ChinaCorrespondence: Yanmei Shen; Xueping Gao, Department of Psychiatry, National Clinical Research Center for Mental Disorders, and National Center for Mental Disorders, The Second Xiangya Hospital of Central South University, Changsha, Hunan, 410011, People’s Republic of China, Email ymshen@csu.edu.cn; xuepinggao@csu.edu.cnBackground: Childhood maltreatment contributes to an increased risk of eating disorders in adolescents. However, less is known regarding the underlying mechanism between childhood maltreatment and eating disorders’ symptoms. This study tested the mediation effect of social anxiety in the association between childhood maltreatment and eating disorders’ symptoms and whether this mediation was moderated by physical activity.Methods: A longitudinal study was conducted among 848 students in grades 7– 8 from a middle school in Changsha, China. The students completed measurements on childhood maltreatment (Childhood Trauma Questionnaire) at the baseline and measurements on social anxiety (The Social Anxiety Scale-Adolescents), physical activity, and eating disorders’ symptoms (The Eating Attitudes Test) after six months. Mediation and moderation analyses were carried out in SPSS macro-PROCESS.Results: Emotional abuse was significantly related to eating disorders’symptoms, and the association was mediated by social anxiety (indirect effect: β =  0.03, 95% CI: 0.01 to 0.05, p< 0.05). Furthermore, physical activities moderated the path of emotional abuse to social anxiety (β = 0.32, 95% CI: 0.25 to 0.39, p< 0.01) and social anxiety to eating disorders’symptoms (β = 0.18, 95% CI: 0.10 to 0.26, p< 0.01).Conclusion: This research emphasizes the importance of social anxiety in the relationship between childhood maltreatment and eating disorders’ symptoms. Additionally, these associations are weaker for adolescents with more physical activities, addressing the importance of physical activity in the prevention and management of eating disorders’ symptoms.Keywords: childhood maltreatment, social anxiety, eating disorders, adolescent, physical activity, moderated mediation model